Altered expression of 3´paralogus HOX A-D clusters in endometriosis disease: A case-control study - Masoumeh Golestan Jahromi; Reza Aflatoonian; Parvaneh Afsharian; Samaneh Aghajanpour; Maryam Shahhoseini; Abbas Aflatoonian (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Endometriosis is a prevalent gynecological disease, with limited known etiology and more researches are required to identify its etiology. In this manner, there is no evidence for expression and function of 3´HOX genes in 4 clusters in the limb and pelvic organs such as the uterus and its disorders (Genes in the HOXA-D clusters are subdivided into 13 paralogous groups). Objective: This study designed to investigate the expression profile of 5 paralogous (1-5) in four clusters of HOX genes (A, B, C, and D) in ectopic and eutopic tissues of women with endometriosis compared to the normal endometrium. Materials and Methods: Samples were obtained from thirty patients (15 with and 15 without endometriosis) of reproductive age with normal menstrual cycles. The same patient provided both eutopic and ectopic tissues and control women were laparoscopically checked for the absence of endometriosis. The expression profile of these HOX genes was investigated by quantitative real-time polymerase chain reaction technique. Results: We observed significant up-regulation of some members of HOXC and D clusters (HOXD1, HOXD3, HOXC4 and HOXC5) in ectopic and eutopic tissues vs. control. Also, our data showed significant down-regulation of all of HOXA and HOXB paralogous except HOXA1 in ectopic tissues versus control. Conclusion: Our data showed specific cluster dependent modulation of the HOX genes expression in endometriosis (over-expression of some HOX genes in cluster C and D and down-regulation of HOX genes in cluster A and B) in ectopic and eutopic tissues compare to control group. Therefore, it is possible that change of expression level of these genes in endometrium plays a role in the pathogenesis of endometriosis.